FORMATION OF CONSUMER ACCOMMODATION MODELS WITH DUE ACCOUNT OF POPULATION INVESTMENT POTENTIAL - I. V. Shaniukevich (Наука и техника)
The paper considers a theme of typological urban housing diversity  which is relevant for a modern residential real estate market. Analyzed Quantitative and qualitative characteristics of the existing urban residential accommodation, new  house building have been analyzed in the paper. The paper presents author’s calculations of differentiation extent and changes in economic opportunities of the population. Differentiation of  potential consumer accommodation models with specific standardized characteristics has been made in terms of the population economic prosperity.  The paper substantiates proposals on accountability and implementation of typological differences in the government housing policy.